Active ingredients of traditional Chinese medicine inhibit NOD-like receptor protein 3 inflammasome: a novel strategy for preventing and treating heart failure - Ruifang Lin; Ruifang Lin; Yunfeng Yu; Lixin Du; Zehui Ding; Zehui Ding; Ziyan Wang; Ziyan Wang; Jiaming Wei; Jiaming Wei; Zhihua Guo; Zhihua Guo (Frontiers in Immunology)
Heart failure (HF) has emerged as a significant global public health challenge owing to its high rates of morbidity and mortality. Activation of the NOD-like receptor protein 3 (NLRP3) inflammasome is regarded as a pivotal factor in the onset and progression of HF. Therefore, inhibiting the activation of the NLRP3 inflammasome may represent a promising therapeutic approach for preventing and treating HF. The active ingredients serve as the foundation for the therapeutic effects of traditional Chinese medicine (TCM). Recent research has revealed significant advantages of TCM active ingredients in inhibiting the activation of the NLRP3 inflammasome and enhancing cardiac structure and function in HF. The study aimed to explore the impact of NLRP3 inflammasome activation on the onset and progression of HF, and to review the current advancements in utilizing TCM active ingredients to inhibit the NLRP3 inflammasome for preventing and treating HF. This provides a novel perspective for the future development of precise intervention strategies targeting the NLRP3 inflammasome to prevent and treat HF.